2004
DOI: 10.1111/j.1600-0447.2004.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying women at‐risk for postpartum depression in the immediate postpartum period

Abstract: The findings suggest that several risk factors for depressive symptomatology in the immediate postpartum period are consistent with previously identified factors but other factors such as recent immigrant status, feeling unready for hospital discharge, dissatisfaction with their infant feeding method, and pregnancy-induced hypertension should also be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
149
3
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(172 citation statements)
references
References 47 publications
13
149
3
7
Order By: Relevance
“…Dennis et al believes that unexpected pregnancy can cause duality towards infant and the infant's denial, both of which can increase the possibility of occurrence of depression in the person. Dennis et al observed that, individuals who decide to have child with previous plans would have a life with more social and economic balance (38). Beck and Gable also reported that there was a significant relationship between preparedness to accept responsibility of an infant and postpartum depression (51).…”
Section: Discussionmentioning
confidence: 99%
“…Dennis et al believes that unexpected pregnancy can cause duality towards infant and the infant's denial, both of which can increase the possibility of occurrence of depression in the person. Dennis et al observed that, individuals who decide to have child with previous plans would have a life with more social and economic balance (38). Beck and Gable also reported that there was a significant relationship between preparedness to accept responsibility of an infant and postpartum depression (51).…”
Section: Discussionmentioning
confidence: 99%
“…The postpartum period is a very important period for women in terms of appearance of mood disorders. These disorders range from sadness and PPD to mania (15). No previous studies were found in this regard in Rafsanjan, Iran.…”
Section: Introductionmentioning
confidence: 91%
“…[59] Depresif belirtisi olan kadınların emzirme konusunda daha fazla kaygılandık-ları, sütlerinin besleyiciliği ve yeterliliği konusunda olumsuz düşüncelere sahip oldukları söylenebilir. [60] Olumsuz bilişler depresif duygudurumun artması-na, depresif ruh hali de olumsuz davranışlara neden olmaktadır. Emzirme konusunda yetersiz olacağı fikrine kapılan anne emzirmeye daha az isteklidir ve bu durum bebek besleme yöntemini etkilemektedir.…”
Section: Gebelik Ya Da Postpartum Dönemdeki Depresyon Ile Emzirme İliunclassified